Estudio de los factores necesarios para la elaboración de la marca turística de la parroquia Vilcabamba cantón Loja - Solórzano Paredes, Nathaly Silvana (2023)
Tourism has become a sector of employment generation and development of a destination, in the same way tourism brands are very important for tourism as they are the promotion of the destination which attracts investment and activates the market. The general objective of this research is to determine the necessary factors for the development of the tourism brand for the parish Vilcabamba of Loja canton in order to achieve a better positioning in the tourism market. Two specific objectives were established: To identify the tourism potential for the Tourism Brand of the Vilcabamba parish of Loja canton, and to establish the factors that will be part of the composition of the Tourism Brand for the Vilcabamba parish of Loja canton. As methodology for the first objective, a bibliographic review of the Vilcabamba parish was made, the interview technique was used to identify the knowledge and perception of the inhabitants of Vilcabamba, in order to validate the variables and then proceed to conduct the survey, which served to know the perception of the people who visit the parish, which in turn allowed to establish the main elements to constitute the brand, also a competition analysis was made. For the second objective, the SWOT matrix was made and finally with all the information obtained, the six-level brand pyramid derived from the Branding methodology for tourist destinations of the World Tourism Organization was elaborated, obtaining as a result the essence of the destination for the generation of a brand in which the main elements were determined as the climate, the mineral properties of the water, the Mandango hill, its long-lived people, finally it is concluded that the Vilcabamba parish by its characteristics has the necessary elements for the creation of a brand.